Po co fantastyka? Kilka uwag na marginesie lektur dawnych i współczesnych - Gemra, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
Works of speculative fiction are among the most often chosen cultural texts. Article indicates several possible reasons of their popularity, such as breaking stereotypes and thinking patterns, inspirations for new solutions, tales of traditional values, chances to immerse in the world of imagination. Dressing an attractive “costume” and speaking an understandable “language”, speculative fiction tells about matters important to the audience. It helps not only to “get away” from reality, but also to reconcile to it and to shape it.